Treatment default and its related factors among tuberculosis patients, a case-control study in Iran - Afshari, Mahdi; Aarabi, Mohsen; Parsaee, Mohammadreza; Nezammahalleh, Asghar; Moosazadeh, Mahmood (German Medical Science GMS Publishing House, 2020)
Introduction: Treatment default is one of the main challenges in tuberculosis (TB) control and is considered a major barrier to achieving the sustainable development goals (SDG). Identifying the factors associated with this outcome can help us provide appropriate strategies for decision making. This study investigates the determining factors of treatment default among TB patients. Methodology: In this case-control study, all 88 TB patients experiencing treatment default during an11-year-period in Mazandaran province, Iran, were compared with 176 randomly selected TB patients without a history of default. Cases and controls were matched based on the year of incidence as well as the treatment center. Related factors of treatment default were determined using multivariate logistic regression models. Results: For men, the odds ratio of experiencing treatment default was 1.67 (p=0.165). In addition, considering ages >64 years as the reference group, the odds ratios for 15- to 24- and 55- to 64-year-olds were 0.95 (p=0.940) and 0.37 (p=0.123), respectively. The corresponding odds ratios for patients 25-34, 35-44 and 45-54 years of age were 1.29 (p=0.547), 1.40 (p=0.472), and 1.39 (p=0.512) respectively. Moreover, the odds ratios for urban residents, patients with a history of imprisonment, a history of previous treatment, adverse treatment effects, previous exposure, non-Iranians and patients with smear-positive TB were 1.72 (p=0.070), 1.24 (p=0.657), 1.47 (p=0.756), 0.99 (p=0.998), 0.98 (p=0.960), 9.29 (p=0.010), and 2.27 (p=0.049) respectively.Conclusion: Non-Iranian nationality and smear-positive TB were detected as predictors of treatment default among patients with tuberculosis.